Information Control on Inventory Study at In One of The Garment Companies in Bandung - Larry Al Bar Hendra Putra; Anton Tirta Komara; Iwan Sidharta; Nita Yura Roslina; Imelda Megawati (Informatics Management, Engineering and Information System Journal, 2023)
The objective of this study is to examine the impact of the Finished Goods Inventory Accounting Information System on the internal control of finished goods inventory at PT. Partners Adi Jaya Manunggal in Bandung City. Based on the obtained calculation results, it has been determined that the Accounting Information System (X) for Finished Goods Inventory is deemed to be of satisfactory quality, as indicated by a score of 3.39. The internal control system for managing finished goods inventory (Y) has demonstrated effective performance, as evidenced by a value of 3.37. The optimization and effective utilization of a precise accounting information system for finished goods inventory is expected to enhance internal control measures for such inventory. The research employed a descriptive verification research method at PT. Partners Adi Jaya Manunggal in Bandung City. In order to gather data and information that will substantiate this research, the approach involves the collection of secondary data and the utilization of linear regression hypothesis testing. This methodology aims to offer a comprehensive understanding of the impact of the Finished Goods Inventory Accounting Information System on the Internal Control System for Finished Goods Inventory. According to the findings of the study, the outcomes of the linear regression analysis indicate that the equation Y = 8.006 + 0.817. This finding indicates that a majority of the population in Mitra Adi Jaya Manunggal, Bandung City, accounts for 63.3%, while the remaining 36.7% represents an unexamined variable of influence.